Corporate Governance - Mallin, Chris A. (Oxford : Oxford University Press, 2007)
Corporate governance is an area that has grown rapidly, fuelled by high profile corporate collapses such as Enron. This is a student-focused text which takes an international approach to the subject.
Previous ed.: 2004.
Includes bibliographical references and index.
Keywords: Corporate governance; Business and Management